Analisis Tentang Wali Adhal Dalam Pelaksanaan Perkawinan (Studi Penetapan Nomor 0029/Pdt.P/PA.Jmb) - Joko Lelono Joko Lelono; Taufik Yahya (Universitas Jambi, Fakultas Hukum, 2021)
The harmony to get married is Article 14 Compilation of Islamic Law. The article explains that the marriage guardian is the pillar that must exist to carry out the marriage. While Article 2 of the Minister of Religion Regulation No. 30/2005 concerning Judge Guardian regulates marriage guardians who do not meet the requirements, are unable or refused (adhal) then the marriage takes place with the guardian of the judge based on the decision of the Religious Court in the bride's residence. The purpose of this study is to find out, analyze the arrangements of marriage guardians who refuse marriage and the consideration of Religious Court Judges in the determination of guardians is for people who want to get married whose guardians refuse to marry. The formulation of this problem is 1) Is the reason the guardian nasab refused to marry his child justified or not according to religious law and legislation? 2) What is the basis for the judge's consideration to grant the application for the determination of guardians regarding case Number 0029 / Pdt.P / 2018 / PA.Jmb? This research method used is normative juridical and the approach used is a conceptual approach, legislation approach, and case approach. The results of this study there are no regulations that specify in detail and also clear what are the justified reasons whether or not a nasab guardian refused to marry. Article 2 of the Minister of Religion Regulation No. 30/2005 only explains the absolute authority of the Religious Courts to hear cases. Abstrak Rukun untuk melangsungkan perkawinan adalah Pasal 14 Kompilasi Hukum Islam. Pasal tersebut menjelaskan mengenai wali nikah adalah rukun yang harus ada untuk melaksanakan perkawinan. Sedangkan Pasal 2 Peraturan Menteri Agama Nomor 30 Tahun 2005 tentang Wali Hakim mengatur mengenai wali nikah yang tidak memenuhi syarat, berhalangan atau menolak (adhal) maka pernikahannya dilangsungkan dengan wali hakim berdasarkan putusan Pengadilan Agama wilayah tempat tinggal mempelai wanita. Tujuan penelitian ini untuk mengetahui, menganalisis pengaturan wali nikah yang menolak menikahkan dan pertimbangan Hakim Pengadilan Agama dalam penetapan wali adhal bagi orang ingin menikah yang walinya menolak menikahkan. Rumusan masalah ini adalah 1) Apakah alasan wali nasab menolak menikahkan anaknya dibenarkan atau tidak menurut hukum agama dan perundang-undangan? 2) Apa dasar pertimbangan hakim mengabulkan permohonan penetapan wali adhal perkara Nomor 0029/Pdt.P/2018/PA.Jmb? Metode penelitian ini yang digunakan yaitu yuridis normatif dan pendekatan yang digunakan adalah pendekatan konseptual, pendekatan perundang-undangan, dan pendekatan kasus. Hasil penelitian ini tidak ada peraturan yang menyebutkan secara rinci dan juga jelas apa saja alasan yang dibenarkan atau tidaknya seorang wali nasab menolak untuk menikahkan. Pada Pasal 2 Peraturan Menteri Agama Nomor 30 Tahun 2005 hanya menjelaskan mengenai kewenangan absolut Pengadilan Agama untuk mengadili perkara.